TikTok as a potential patient educational tool for thyroid-associated ophthalmopathy: A cross-sectional study - Yue Wang; Shuo Yang; Xingyi Shu; Yuqing Chen; Ruili Wei (Digital Health)
Objective Thyroid-associated ophthalmopathy (TAO) is a prevalent orbital disease significantly affecting patients’ daily lives. Nowadays, TikTok acts as a novel tool for healthcare but involved videos need to be further assessed. Many individuals search for disease information on TikTok before professional consultation. This study aimed to assess the quality of TAO-related TikTok videos and correlations between video variables and quality. Methods The top 150 TikTok videos were collected using the keyword TAO. Duplicate, too-short, irrelevant videos and similar videos from the same source were excluded. Two raters evaluated the included videos’ overall quality, reliability, understandability, and actionability on different sources and content focuses. Results Ninety videos had received nearly 15,000 likes and 2000 shares. Ophthalmologists and treatment focus were two primary parts among categorized groups, whose quality scores were much higher than others. The average Patient Education Materials Assessment Tool for Audiovisual Materials scores, Global Quality Scores, and DISCERN scores indicated that these videos were easy to understand (87.6%), actionable (74.5%), and fair in quality (44.97). The number of added hashtags was an essential variable positively correlated with video understandability. Additionally, popularity showed negative correlations with the overall quality, while video length positively correlated with its reliability and negatively correlated with the uploaded days. Conclusion Certified healthcare professionals uploaded most TAO videos, resulting in acceptable quality with minimal misinformation. To serve as a qualified source of patient educational materials, TikTok is supposed to promote longer disease-related videos and enhance reliability and understandability simultaneously.